Clinical perception and novel insights of chronic myelomonocytic leukemia: a 10-year multi-center retrospective study - Liu, Yanquan; Yan, Zhimin; Zhang, Jingdong; Chen, Xiaojun; Shen, Jianzhen; He, Honghua; Yin, Yue; Guo, Huidong; Zeng, Fanlin (Frontiers in Medicine, 2026)
Background and objectiveChronic myelomonocytic leukemia (CMML) is a malignant clonal disorder characterized by both myelodysplastic syndrome (MDS) and myeloproliferative neoplasm (MPN) features. Due to its relatively low incidence, there remains a lack of consensus regarding diagnostic criteria and therapeutic strategies within the academic community, which poses significant challenges in clinical management. This study aims to investigate the clinical manifestations, diagnostic approaches, therapeutic interventions, and prognostic factors associated with CMML, with the goal of providing evidence-based insights for future basic research and clinical practice in the field of hematology.MethodsClinical data from 271 CMML patients treated at five tertiary hospitals between January 2015 and May 2025 were collected and analyzed. The clinical characteristics, treatment modalities, and outcomes were systematically reviewed. Comprehensive prognostic evaluation was conducted using the Kaplan–Meier method, Log-rank test, and Cox proportional hazards regression model.ResultsA total of 271 CMML patients were enrolled, including 178 males (65.68%) and 93 females (34.32%), with a median age at diagnosis of 66 years (range: 26–89). According to the FAB classification, 109 cases (40.22%) were classified as myelodysplastic-type CMML (MD-CMML), and 162 cases (59.78%) as myeloproliferative-type CMML (MP-CMML). Based on the WHO classification, the distribution was as follows: 59 cases (21.77%) of CMML-0, 66 cases (24.35%) of CMML-1, and 146 cases (53.87%) of CMML-2. First-line treatment primarily involved chemotherapy, while 107 patients received only supportive care. Treatment response was evaluable in 199 patients: 97 cases achieved complete remission (CR), 63 cases achieved partial remission (PR), 32 cases had stable disease (SD), and 7 cases experienced disease progression (PD). Follow-up was completed by June 30, 2025. Among the 271 patients, 159 cases (58.67%) were alive, 97 cases (35.79%) had died, and 15 cases (5.54%) were lost to follow-up. The median overall survival (OS) was 23.5 months (range: 0.5–109). Multivariate analysis identified that factors associated with poor OS included elevated neutrophil count, increased monocyte count, decreased hemoglobin (HB) levels, elevated lactate dehydrogenase (LDH), increased β2-microglobulin (β2-MG), and peripheral blood blast count ≥5% (p < 0.05), while the decreased HB and peripheral blood blast count ≥5% was independent adverse prognostic factors for OS.ConclusionCMML is a highly heterogeneous disease with generally unfavorable clinical outcomes. Although chemotherapy can induce remission in some cases, long-term survival remains limited. The enrollment in clinical trials should be encouraged to improve patient prognosis.